Exploration of intelligent education method:mobile game assisted research teaching - Hao SHENG; Li RUAN; Ke XU; Jun HAN; Zhang XIONG; Xiaopeng GAO; Weifeng LYU (物联网学报)
The technology of intelligent IoT and ubiquitous access lead to the change of the learning mode.The traditional mobile phone assisted teaching mode just simply transplants some contents of classroom teaching to the Internet terminal,which does not give full play to the flexibility and interest of the mobile intelligent terminal.Based on the fragmentation of learning content and the innovation of mobile communication technology,a ubiquitous learning theory oriented to auxiliary teaching was proposed,which made full use of the advantages of fragmentation time and mobile learning and made fragmented learning possible.Then,the feasibility of game assisted teaching was demonstrated,including the collaborative learning network,situational cognitive theory and ubiquitous learning.In addition,a learner-centered game assisted teaching model was proposed,which consists of three parts including game assisted teaching strategy,learner and teaching design model.It pays more attention to the realization of expected teaching objectives and the maintenance of learning stickiness.Finally,the feasibility and effectiveness of ubiquitous learning theory were verified by the experimental results of two courses of mobile phone assisted teaching,which makes mobile game assisted teaching a useful supplement to traditional classroom teaching.